POLITICAL COMMUNICATION AND POP CULTURE: THE INFLUENCE OF SOCIAL MEDIA ON THE COMMUNICATION STYLE OF POLITICAL CANDIDATES - Abdul Rahman (Penelitian dan Pengembangan Ilmu, 2025)
Social media has transformed the contemporary political communication landscape, making it a key arena for candidates to build rapport with the public. In Indonesia, with over 70% of the population using social media and the dominance of platforms like TikTok and Instagram, social media serves not only as a space for entertainment but also as a political battleground. This phenomenon has given rise to the integration of popular culture—memes, viral music, slang, and even fashion—into candidates' communication styles, particularly to appeal to the younger generation, who make up the majority of users.This study uses a narrative review approach to literature from 2010–2025 from Scopus, Web of Science, and Google Scholar. The analysis highlights themes of mediatization, personalization, populism, and cultural hybridity. Findings show that social media encourages candidates to appear more personal, casual, and relatable through humor, storytelling, and popular culture symbols. This strategy is effective in increasing engagement, but risks diminishing credibility if the substantive message is ignored.